Foscarnet calcium microcrystals as the intravitreal drug depot. Issue 37 (24th April 2017) - Sun, Yuling; Tao, Yong; Cao, Qingchen; Huang, Yanbin
Abstract : Injectable foscarnet calcium microcrystals can maintain the intravitreal drug concentration for months. Abstract : Foscarnet sodium is an antiviral drug for the treatment of CMV retinitis, currently in the form of twice-weekly intravitreal injection. Here we developed foscarnet calcium microcrystals as the drug depot, and using the rabbit model we demonstrated that the injected microcrystals maintained a therapeutically relevant drug concentration in the vitreous for more than 3 months.